The Effect of SOEs Supervisory Organs on the Improvement of Internal Control in Public Sector Companies - Lenda, Komala (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Weak internal control in public sector companies often leads to fraud, such as asset misappropriation and corruption, threatening the management of state assets. This study aims to examine the effectiveness of the board of commissioners or supervisory board and the audit committee in improving internal control within Indonesian state-owned enterprises. A quantitative descriptive approach was used, collecting primary data through questionnaires distributed to 60 state-owned enterprises selected via purposive sampling. Data were analyzed using path analysis to measure the influence of these supervisory bodies. The findings show that the board of commissioners or supervisory board and the audit committee, individually and together, positively impact internal control, contributing 53.34% to its improvement, with the board having a stronger effect (32.31%) than the audit committee (6.20%). These efforts enhance operational efficiency, financial reporting reliability, and regulatory compliance, reducing fraud risks. In conclusion, effective oversight by these bodies strengthens internal control systems, but challenges like political affiliations require further attention. This study highlights the need for improved coordination and independence to enhance governance and prevent fraud in state-owned enterprises.